Perbedaan Perkembangan Psikologis Anak Antara Anak Yang Dibesarkan Di Lingkungan Perkotaan Dan Pedesaan - Awiting Kembang Jagat Putrantiwi; Titis Puspa Agnes Saputri; Benta Ferdinan; Mahilda Dea Komalasari (JURNAL ILMIAH NUSANTARA, 2025)
Child psychological development is influenced by various factors, one of which is the environment in which they grow and develop. This study aims to analyze the differences in the psychological development of children raised in urban and rural environments, focusing on their social, emotional, and cognitive aspects. Urban and rural environments offer different conditions that affect children's development, including access to education, technology, and parenting styles. Children in urban areas tend to be more advanced in cognitive development due to greater access to education and technology, but they are more vulnerable to stress and anxiety due to social pressures. On the other hand, children in rural areas possess better social skills due to closer interaction with the community but are limited in access to educational resources and technology, which affects their cognitive development. The research method used is descriptive-comparative with a quantitative and qualitative approach. Data were collected through questionnaires, interviews, and direct observations involving children, parents, and teachers from both environments. The research findings indicate that although children in urban areas have greater access to facilities and technology, they face higher stress levels, whereas children in rural areas tend to have lower anxiety and better social skills, but are limited in terms of formal education. This study provides valuable insights for the development of inclusive educational policies and parenting styles that consider the contextual environment of children in order to optimally support their psychological development.